PENGARUH MINAT DAN MOTIVASI BELAJAR MAHASISWA TERHADAP PRESTASI MAHASISWA PGMI UNISLA - Ummu Khairiyah (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The purpose of this study is to analyze the influence of interest and learning motivation on student achievement in lectures in the IPA 2 course at the PGMI Study Program in Universitas Islam Lamongan. The sample in this study were 85 students. The method used in this research is a quantitative approach. data collection techniques used questionnaire and documentation techniques. Data analysis techniques used are using SPSS type 25 with multiple linear regression to determine whether there is an influence of interest and motivation on student achievement. Simultaneous test data results (Test F) show that the score where Fcount = 47.706 is greater than Ftable = 3.35 or Fcount = 47.706> Ftable = 3.35. Partial Test Results (T Test) obtained a sig value of 0,000, which means that the t test here shows no effect because the sig value <0.05. From the two tests above it can be concluded that there is a significant influence between interest and motivation to learn on student learning outcomes